From the Traditional Spot to the Reel on Instagram: Evolution of Advertising in Sportswear Brands - Jiménez Sánchez, Álvaro; Margalina, Vasilica-Maria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research conducted a content analysis of 117 YouTube spots and 117 Instagram reels with the most views for Nike, Adidas, Puma, Reebok and Converse brands. Data shows that reels last less time, contain less violence, less use of celebrities and greater gender and age variety. Also, they have more animations, higher views, likes and passive engagement (likes/views), but less mixed engagement ((comments/likes)/views) than YouTube. In addition, correlations are found between certain variables and the different types of effectiveness. All of this is useful for this type of brands to improve their audiovisual commercial strategies.